Underemployment among Mature‐Age Workers in Australia1. Issue 295 (23rd September 2015) - Li, Jinjing; Duncan, Alan; Miranti, Riyana
Abstract : Underemployment is a serious and pervasive problem both in terms of its impact on those individuals affected, and for the economy as a whole. Underemployment is associated with job insecurity, increased casualisation and lower savings, and from a macroeconomic standpoint, underemployment is a signal of inefficiency in the utilisation of skilled labour. This article explores the patterns of underemployment for mature‐age workers in Australia, a group for whom the prevalence of long spells of underemployment is especially marked. The research uses a 12‐year panel dataset to analyse factors that contribute to a heightened risk of underemployment. Significant path dependency is revealed, whereby previous periods of underemployment increase the propensity towards further underemployment in the current period. Interestingly, most demographic and socioeconomic characteristics, except for the presence of older dependent children and a non‐English‐speaking foreign‐born background for women, tend not to have any direct impact on the propensity for underemployment. These findings suggest the need for targeted interventions to triage these barriers aimed at highlighting the role of improved labour market attachment in promoting the well‐being and economic contribution of mature‐age workers.